2017
DOI: 10.1111/pbaf.12170
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of the Management's Discussion and Analysis to Citizen Users of Government Financial Reports

Abstract: This study focuses on the accessibility of Management's Discussion and Analysis (MD&A), a key part of the GASB 34 financial reporting framework. We analyze MD&As extracted from Comprehensive Annual Financial Reports issued by the 50 state governments to answer the question: How accessible is the MD&A to citizen users of government financial reports? Using three dimensions of accessibility—size, readability, and timeliness—our results point to the inadequacy of MD&As in providing information to citizens about g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
0
17
0
3
Order By: Relevance
“…Smith and Smith (1971) found that in order to understand annual report footnotes, readers require at least some college-level education to ensure access to the information contained therein. These findings were later echoed by Yusuf and Jordan (2017) who examined government Management Discussion and Analysis reports. Other researchers have investigated the readability of letters to shareholders (Subramanian et al, 1993), 10-K and 10-Q reports (Lee, 2012;Li, 2008;Miller, 2010) finding that more readable reports are related to better-performing firms, more persistent earnings, higher trading activity, and stock prices that are better able to absorb information.…”
Section: Readability Of Financial and Csr Reportsmentioning
confidence: 90%
“…Smith and Smith (1971) found that in order to understand annual report footnotes, readers require at least some college-level education to ensure access to the information contained therein. These findings were later echoed by Yusuf and Jordan (2017) who examined government Management Discussion and Analysis reports. Other researchers have investigated the readability of letters to shareholders (Subramanian et al, 1993), 10-K and 10-Q reports (Lee, 2012;Li, 2008;Miller, 2010) finding that more readable reports are related to better-performing firms, more persistent earnings, higher trading activity, and stock prices that are better able to absorb information.…”
Section: Readability Of Financial and Csr Reportsmentioning
confidence: 90%
“…The formula has been "popularised" in corporate report readability research (Courtis, 2004, p. 297) and continues to be widely used in readability studies of annual report narratives and other written corporate communications (e.g. Melloni et al, 2017;Yusuf and Jordan, 2017;Cheung and Lau, 2016;Moreno and Casasola, 2016). Using the formula facilitates linkages with the substantial corpus of corporate report readability research which utilises the measure.…”
Section: Readability Of Integrated Reportsmentioning
confidence: 99%
“…Additional tests were conducted using the Fog Index and Flesch-Kincaid Grade level, measures commonly used in corporate report readability studies and as tests of robustness in conjunction with Flesch (e.g. Wang et al, 2018;Melloni et al, 2017;Yusuf and Jordan, 2017;Cheung and Lau, 2016;De Franco et al, 2015). The Fog Index is: (words per sentence + per cent of complex words)×0.4, where complex words contain three or more syllables (Li, 2008).…”
Section: Readability Of Integrated Reportsmentioning
confidence: 99%
“…Although GASB limits MD&A to a list of topics, it encourages governments to effectively report only the most relevant information customized for the local community. That is, the MD&A section is essential for government financial transparency because it enables a non‐expert citizen or policymaker to obtain a basic understanding of the financial condition of their local government (Yusuf and Jordan 2017).…”
Section: Government Financial Reporting and Auditingmentioning
confidence: 99%